Irregular Appointment of Emploees and Excess Pay Payment in Chhattisgarh Medical Services Corporation - CAG of India (CAG of India)
The Company has appointed employees on Samvida basis without approved set-up and also made payment of higher consolidated pay in violation of Government rules and directives which has resulted in excess payment of ₹ 56.98 lakh.